Karl Barth, Kirchliche Dogmatik, IV, 3: The Doctrine of Reconciliation, Part 3 - Bromiley, G. W. (Scottish journal of theology, 1962)
There is good hope that the present year will see the appearance of the English translation of IV, 3 of the Church Dogmatics, and with it the conclusion of the doctrinal treatment of the atonement1 and the publication of all the Dogmatik thus far available. Necessarily divided into two halves because of its great length, this third part is devoted to the prophetic work of Jesus Christ in reconciliation. It thus represents an original attempt on the part of the author to work out in detail a theme which has often been suggested in earlier theology, but which has never been given the treatment accorded to the priestly work on the one side or the kingly work on the other.